Business intelligence in organizational decision-making: a bibliometric analysis of research trends and gaps (2014–2024) - Sabri Mekimah; Rahma Zighed; Khaled Mili; Ismail Bengana (Discover Sustainability)
Abstract This study examines the evolving landscape of Business Intelligence (BI) research and its impact on organizational decision-making through a comprehensive bibliometric analysis. Analyzing 2442 BI-related articles from the Scopus database published between 2014 and 2024, we identified key trends, influential authors, leading institutions, and significant research gaps. Despite substantial literature, our findings reveal a declining trend in BI publications and significant under-exploration in integrating BI with competitive intelligence, decision-making processes, data mining, and human resources management. The study highlights geographical disparities in research output, with the United States and China leading in publications and citations. Our analysis underscores the need for more interdisciplinary research approaches and increased collaboration among researchers and institutions to address these gaps. This study provides valuable insights for researchers and practitioners, offering direction for future research to enhance the application of BI in organizational decision-making and strategic development.